Formation of Au/Pd–Sn trimetallic particles onto vitreous carbon - Meier, Lorena Alejandra (2013)
The sequential deposition process of Pd and Sn on Au microcrystals, previously electrodeposited onto vitreous carbon (VC) was investigated in sulphuric acid solution by cyclic voltammetry and Auger electron spectroscopy (AES). Scanning electron microscopy was used to characterize Au deposits. The results reveal that the deposition of Pd and Sn is selective on the Au microcrystals, uniformly distributed on the VC surface, due to the strong interaction energy between the three metals. From the cyclic voltammetric and AES measurements in the VC/Au/Pd/Sn system, the existence of a Sn core–shell structure with Pd can be inferred. Similar voltammetric results were obtained for the VC/Au/Sn/Pd system, where in this case, the Pd adsorbed layer screened the Sn deposits on the VC/Au interface. However, the AES spectrum shows that Sn is still present on the surface, indicating that probably, the Sn deposits have diffused to the surface, or they are not completely covered by Pd. The VC/Au/Pd/Sn modified substrate appears as an interesting electrocatalyst material for the reduction of nitrate ions.